Normative Method of Strategic Cost Management in the Supply Chain at the Stage of Product Development - Vladimir Nikolaevich Nesterov; Dina Gennadevna Yankovskaya; Natalia Nikolaevna Kozlova (International Journal of Supply Chain Management, 2020)
Abstract— This paper is devoted to the research and application of normative method of management on target costs in supply chain management. The normative method is a widespread method among foreign companies, but Russian enterprises apply this method not often because of its possible using difficulties. Two aspects of using this method are presented and problems of standards determination are revealed in this study, i.e. at the stage of development product and the stage of it output in supply chain process. Besides that, the existence of conception by management on target costs are discovered and the concrete procedures for application of target norms are presented. The authors lay great stress on control system of enterprise, so for this purpose the algorithm of normative control forming on responsibility centers are developed and presented by scheme. The results of this study allow to increase the competitiveness and the efficiency of enterprise’s activity through cost management in the supply chain process.